2010
DOI: 10.1111/j.1541-0072.2009.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Greening America's Skylines: The Diffusion of Low‐Salience Policies

Abstract: The diffusion literature is replete with examples of highly salient policies spreading across subnational governments. However, low‐salience policies that do not benefit from a groundswell of public opinion also spread across jurisdictions in patterns that appear similar to those of other, more well‐known policy ideas. This research is an investigation of the mechanisms that propagate low‐salience policies. I analyze the adoption of the U.S. Green Building Council's (USGBC) Leadership in Energy Efficient Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 61 publications
1
39
0
4
Order By: Relevance
“…As consumers and producers of goods and services, governments have an ability to shape policy outcomes outside the legislative policy process in what we term “policy by doing.” We conceptualize “policy by doing” as decision making by governments (as a function of policy or not) whose actions are intended to influence the decisions of target groups—community members, businesses, etc—absent or in addition to legislative policies to address such behavior. “Policy by doing” employs mechanisms for exhorting behavioral chance found in literatures on leadership (Koski, ), regulatory pre‐emption (King & Lenox, ), and the capacity of governments to reduce risk for firms by way of market creation (Gulbrandsen, ). “Policy by doing” can be an attempt to shape outcomes via an administration's specific policies—e.g., the city of Portland will no longer use Styrofoam—or an attempt to influence other community actor behaviors by setting examples that are not legislative policies—e.g., mandatory recycling in all state agencies will act as an example but also serve to decrease the amount of recyclable material that enters into the waste stream.…”
Section: Introductionmentioning
confidence: 99%
“…As consumers and producers of goods and services, governments have an ability to shape policy outcomes outside the legislative policy process in what we term “policy by doing.” We conceptualize “policy by doing” as decision making by governments (as a function of policy or not) whose actions are intended to influence the decisions of target groups—community members, businesses, etc—absent or in addition to legislative policies to address such behavior. “Policy by doing” employs mechanisms for exhorting behavioral chance found in literatures on leadership (Koski, ), regulatory pre‐emption (King & Lenox, ), and the capacity of governments to reduce risk for firms by way of market creation (Gulbrandsen, ). “Policy by doing” can be an attempt to shape outcomes via an administration's specific policies—e.g., the city of Portland will no longer use Styrofoam—or an attempt to influence other community actor behaviors by setting examples that are not legislative policies—e.g., mandatory recycling in all state agencies will act as an example but also serve to decrease the amount of recyclable material that enters into the waste stream.…”
Section: Introductionmentioning
confidence: 99%
“…Second, city governments may lack the technical expertise needed to develop effective policies for promoting, or requiring, building energy retrofits (Betsill, ; Koski, ). While a major selling point for such policy innovations is the potential for energy savings at the individual or building owner level, such savings are often uncertain and must be estimated using various technical models (Mills, ).…”
Section: Cities and Climate Change Policy: Energy Efficiency Retrofitsmentioning
confidence: 99%
“…Finally, those interested in furthering energy efficiency policies can face challenges mobilizing and leveraging the political will needed for developing and supporting new funding and new approaches. Energy efficiency is considered a “low salience” policy issue, as it typically receives very little attention from the public and generates relatively little conflict (Koski, ). While in some ways the lack of conflict or contention around energy efficiency can be advantageous—there are few interest groups explicitly opposed to energy efficiency—it also means demand for energy efficiency policy innovations can be diffuse and tied to broader environmental concerns and measures.…”
Section: Cities and Climate Change Policy: Energy Efficiency Retrofitsmentioning
confidence: 99%
“…Roberts and King's typology (1991) served as a useful heuristic to categorize public entrepreneurs, but researchers have suggested additional types or more nuanced policy actors, such as Koski's (2010) facilitative "knowledge brokers" and Crow's (2010) "policy experts". Informants in Massachusetts (one of the later adopters of broad-based merit aid) provided evidence of policy experts seeking to shape the form that the scholarship program would take in the Commonwealth.…”
Section: Implications For Future Research and Policymentioning
confidence: 99%
“…Crow found that "policy experts" (e.g., attorneys) were policy entrepreneurs key to bringing about changes in water rights policies in Colorado. Koski (2010) has drawn a distinction between policy entrepreneurs and knowledge brokers such that policy entrepreneurs are those who emphasize and utilize specific types of political tactics, such as lobbying, to spread an innovation. Knowledge brokers utilize a facilitative approach by translating and communicating complex aspects of technical standards.…”
Section: The Role Of Public Entrepreneurs In the Diffusion Of Innovatmentioning
confidence: 99%